La crisis del Sistema partidario peruano (1985-1995) - Crabtree, John (1994)
In this essay the author seeks to examine political development in Peru since the late 1980's, especially since Alberto Fujimori's election as the president of Peru. It focuses on the breakdown of the Peruvian political party system (its existence and the political parties' roles), as well as the most critical problems in the last few years: hyperinflation and terrorism. Finally, it discusses the conditions under which the party system might be revived.